Loss of skeletal muscle during neoadjuvant chemotherapy is related to decreased survival in ovarian cancer patients. Issue 4 (7th March 2016) - Rutten, Iris J.G.; van Dijk, David P.J.; Kruitwagen, Roy F.P.M.; Beets‐Tan, Regina G.H.; Olde Damink, Steven W.M.; van Gorp, Toon
Abstract: Background: Malnutrition, weight loss, and muscle wasting (sarcopenia) are common among women with advanced ovarian cancer and have been associated with adverse clinical outcomes and survival. Our objective is to investigate overall survival (OS) related to changes in skeletal muscle (SM) for patients with advanced ovarian cancer treated with neoadjuvant chemotherapy and interval debulking. Methods: Ovarian cancer patients ( n  = 123) treated with neoadjuvant chemotherapy and interval debulking in the area of Maastricht (the Netherlands) between 2000 and 2014 were included retrospectively. Surface areas of SM and adipose tissue were defined on computed tomography at the level of the third lumbar vertebra. Low SM at baseline and SM changes during chemotherapy were compared with Kaplan Meier curves, and Cox‐regression models were applied to test predictors of OS. Results: Median OS for patients who lost SM ( n  = 83) was 916 ± 99 days, which was significantly different from median OS for patients who maintained or gained SM ( n  = 40), which was 1431 ± 470 days ( P  = 0.004). Loss of SM was also a significant predictor of OS in multivariable Cox‐regression analysis (hazard ratio 1.773 (95%CI: 1.018–3.088), P  = 0.043). Low baseline SM did not influence survival. Conclusions: Patients with ovarian cancer have a worse survival when they lose SM during neoadjuvant chemotherapy. Evaluation of low SM at a specific time point is not prognostic for OS. External and prospective validation of these findings is imperative. Nutritional, pharmacological, and/or physical intervention studies are necessary to establish whether SM impairment can be prevented to prolong ovarian cancer survival.